PERLINDUNGAN HUKUM DATA PRIBADI DALAM KEGIATAN BISNIS DI INDONESIA - Trifena Sandag, Gabrily; Janpieter Hutajulu, Marihot (Kertha Semaya : Journal Ilmu Hukum, 2022)
As mandated in Article 28 G paragraph (1) and Article 28 H paragraph (4) of the 1945 Constitution of the Republic of Indonesia (the constitution). Despite the fact that there is already a presence or regulation regarding the protection of personal data in several laws, namely as Law Number 7 of 1992 concerning Banking as amended by Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking; Law Number 36 of 1999 concerning Telecommunications; Law Number 43 of 2009 concerning Archives; Law Number 11 of 2008 concerning Information and Electronic Transactions (“ITE Law”) as amended by Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions; Minister of Communication and Information Technology Regulation Number 20 of 2016 Protection of Personal Data in Electronic Systems, with the reasons mentioned in the Law that the author has described above, there have been widespread cases starting from the cases of Tokopedia, Lazada and etc. Regarding the legal issues above, the author's thesis will discuss the Personal Data Bill which will be divided below as follows: The systematic discussion in this paper is divided into two parts. The first part will explain the issue of the Ius constitutum, which is a positive law currently in force in the protection of personal data and a number of laws currently in force which the authors have described above. The second part, while the ius constituendum is a law that is aspired to in the future, such as the Personal Data Bill .